Physical properties of layered FeIn₂Se₄ single crystals - Boledzyuk, V.B.; Kovalyuk, Z.D.; Kudrynskyi, Z.R.; Ivanov, V.I.; Shevchenko, A.D. (Functional Materials, 2016)
Single crystals of FeIn₂Se₄ having a hexagonal structure and mirror-like cleaved surfaces were grown by the Bridgman method. X-ray spectroscopic analysis of the grown crystals was carried out. The morphology of their surface FeIn₂Se₄ was investigated by means of atomic-force microscopy. Temperature dependence of conductivity was measured in the range of 80 - 385 K. It was established the existence of the hysteresis loop of the layered crystals FeIn₂Se₄ at the room temperature.